Unveiling Audit Quality: The Impact of Internal and External Factors With Dysfunctional Auditor Behavior as A Moderating Variable - Anjelia, Rengga; Ali, Syahril (Jurnal Informatika Ekonomi Bisnis, 2024)
This research is designed using behavioral accounting research with a quantitative approach. The research sample was 83 respondents at the BPKP Representative Office of West Sumatra Province obtained through a multi-stage sampling procedure. Model and hypothesis testing using SEM-PLS. Empirical results show that locus of control and professional commitment show a significant and positively correlated effect on audit quality. Time Budget Pressure and workplace spirituality show an insignificant effect on audit quality. Auditor acceptance of the occurrence of audit dysfunctional behavior has a negative and significant effect on audit quality. The variable audit dysfunctional behavior is unable to moderate the effect of locus of control, professional commitment, time budget pressure, and workplace spirituality on audit quality. Although audit dysfunctional behavior does not significantly act as a moderating variable, this study contributes to BPKP in monitoring audit quality, by encouraging the optimization of the implementation of BPKP policy Number 2 of 2023 concerning the Management of Supervisory Assignments.